2015
DOI: 10.7763/ijssh.2015.v5.599
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Better Health Care Services for Mental Health Patients in Malaysia

Abstract: Abstract-The purpose of this research is to explore the mental health services provided by caregivers of a community based rehabilitation centre and the problems encountered by the mentally ill patients. It also sought to propose ways to further improve the psychological well being of the patients in the centre. A narrative inquiry approach and an in depth interview were chosen to get in touch with the social relationship of these patients with their caregivers. The findings revealed the need for more caring, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The health system struggles with the recruitment of new nurses and to retain those who are already part of the system. The persistent problem of untrained mental health caregivers and the resulting sense of frustration and dissatisfaction among patients in the community was highlighted by Low and Lee (2015). Chong et al (2013) also reported that lack of knowledge, and lower mental health literacy posed challenges to family caregivers, mental health service users and service providers in Malaysia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The health system struggles with the recruitment of new nurses and to retain those who are already part of the system. The persistent problem of untrained mental health caregivers and the resulting sense of frustration and dissatisfaction among patients in the community was highlighted by Low and Lee (2015). Chong et al (2013) also reported that lack of knowledge, and lower mental health literacy posed challenges to family caregivers, mental health service users and service providers in Malaysia.…”
Section: Discussionmentioning
confidence: 94%
“…In Malaysia, little is known about the education and training needs, perceived competence, priorities and expectations of mental health nurses who work in mental health services. Low and Lee (2015) have argued that if the services in Malaysia were to achieve the optimal standard for mental health, consideration must be given to how well the workforce is trained and the skills must be advanced to provide quality care.…”
Section: Introductionmentioning
confidence: 99%
“…One relevant way of integrating mental health treatment into the community would be to use more mobile units 16,53 which are likely to be effective during and after COVID-19. For a number of years, Malaysia has had some mobile psychiatry teams that provide services in people's homes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been a number of challenges to fulfilling the ideals of this policy, including financial and coordination issues, a limited number of trained professionals, disagreements between stakeholders, and "lack of participation of social organizations to serve the social needs of people with mental illness" 11 (p. 284). The lack of well-trained mental health professionals and even fewer specialists in Malaysia has been commented upon previously by a number of researchers 16,17 . Malaysia has a population of approximately 32.37 million people 18 , yet as recently as 2018 there were only 410 psychiatrists, a ratio of 1.27:100,000, which is much lower than the WHO's recommended number of 1:10,000 11 .…”
Section: Mental Health and Provision Of Care In Malaysiamentioning
confidence: 99%
“…Moreover, past qualitative studies have been conducted in exploring the life experiences and perspectives of the people with mental health problems (Buizza et al, 2007;Crabtree, 2004;Dinos et al, 2004;Gilburt, Rose, & Slade, 2008;Granerud & Severinsson, 2003;Hanafiah & Bortel, 2015;Johnson et al, 2004;Longo & Scior, 2004;Low & Lee, 2015;Manuel, Hinterland, Conover, & Herman, 2011;Owen, Repper, Perkins, & Robinson, 1998). Within these literatures, the role of reflexivity is relatively uncommon.…”
Section: Reflexivity In Mental Health Researchmentioning
confidence: 99%